2005
DOI: 10.1021/nl051685+
|View full text |Cite
|
Sign up to set email alerts
|

Field-Effect Transistors Based on Self-Organized Molecular Nanostripes

Abstract: Charge transport properties in organic semiconductors depend strongly on molecular order. Here we demonstrate field-effect transistors where drain current flows through a precisely defined array of nanostripes made of crystalline and highly ordered molecules. The molecular stripes are fabricated across the channel of the transistor by a stamp-assisted deposition of the molecular semiconductors from a solution. As the solvent evaporates, the capillary forces drive the solution to form menisci under the stamp pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
102
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 14 publications
2
102
0
Order By: Relevance
“…Patterning organic semiconductors is beneficial because it reduces or eliminates parasitic current paths (crosstalk) between neighboring devices, and results in a significant decrease in the ''off'' current. [9][10][11][12][13][14][15][16] Thin films of polymeric materials are usually prepared from solution, and can be patterned using various techniques such as screen printing, inkjet printing, molding, etc. [17][18][19][20][21][22] Small-molecule semiconducting materials have good thermal and chemical stability and typically exhibit better performance than polymers.…”
mentioning
confidence: 99%
“…Patterning organic semiconductors is beneficial because it reduces or eliminates parasitic current paths (crosstalk) between neighboring devices, and results in a significant decrease in the ''off'' current. [9][10][11][12][13][14][15][16] Thin films of polymeric materials are usually prepared from solution, and can be patterned using various techniques such as screen printing, inkjet printing, molding, etc. [17][18][19][20][21][22] Small-molecule semiconducting materials have good thermal and chemical stability and typically exhibit better performance than polymers.…”
mentioning
confidence: 99%
“…S1 in the Supporting Information). The formation of thin deposits has been studied for series of similar oligomers, [29,30] which revealed that the self-assembly at surfaces is mainly governed by the molecule-molecule (or inter-segment) interactions and the molecule-substrate interactions, and leads to well-defined nanostructures, either 2D ultrathin regular layers or 1D fibrillar objects.…”
mentioning
confidence: 99%
“…It has especially attracted attention when it crystallizes in large, spherical arrangements of twelve calixarene anions residing on the vertices of an icosahedron or cuboctahedron, respectively, the former mimicking the geometry of the many viruses [1,2]. Here we report a variety of novel arrangements of the p-sulfonatocalix [4]arene anion some of which include large, multi-component assemblies not conforming to the geometries of the previously reported Platonic and Archimedean solids.…”
Section: Fa4-ms04-p11mentioning
confidence: 86%
“…Examples are inkjet or coating methods using molecules in solution. It is well established that texture can be induced by crystallisation from solvent in confined geometries with substantial impact on the charge transport properties of organic semiconductors [1]. We present two cases that may be regarded as laboratory equivalents of the "slot die" and the "immersion/dip coating" techniques of the coating industry, and demonstrate the self-organization effect of these techniques.…”
mentioning
confidence: 97%